Socio-Psychological Factors in the Development of Emotional Intelligence of Drug Addicts - Smokova, Liudmyla; Zhylin, Mykhailo; Mendelo, Viktoriia; Kyrylishyna, Maryna; Danilova, Olena (International Journal of Statistics in Medical Research, 2023)
Drug addiction is a current global problem, which causes significant damage to the individual and society as a whole. Drug addicts have numerous disorders, among which the emotional sphere occupies an important place. Identification of social and psychological factors affecting the development of emotional intelligence of drug addicts will make it possible to optimize their psychological rehabilitation programmes. The aim of the study is based on establishing the influence of social and psychological factors on the development of the emotional intelligence level in drug addicts. Methods: The research programme uses standardized psychometric diagnostic methods (MSPSS, Self-Monitoring Scale, EQ-test, Self-esteem test). Descriptive statistics, the Kruskal-Wallace H test, and Pearson’s linear correlation coefficient were used. The Results: The study showed that a low level of emotional intelligence prevails among the surveyed drug addicts (M=37.63±13.38). At the same time, people with a low level have pronounced signs of low social self-control (Н=67.64, р≤0.001), social support (Н=67.76, р≤0.001), and self-esteem (Н=89.12, р≤0.001). Correlation analysis revealed a close direct relationship between emotional intelligence and social self-control (r=0.681, p≤0.001), social support (r=0.632, p≤0.001), and self-esteem (r=0.726, p≤0.001). Conclusions: The study found that the development of emotional intelligence of drug addicts is influenced by such social and psychological factors as social self-control, social support, and self-esteem. These factors determine the ability to manage emotions, adequately perceive them and objectively express them. Prospects: The identified results can be used when building a system of psychological rehabilitation for persons with drug addiction. In particular, to develop emotional intelligence, and improving general emotional well-being.